Fostering Zero Waste Communities: A Participatory Action Research Approach to Implementing 3R Principles in a Suburban Indonesian Village - Suroto S; Vega Candra Dinata; Fifukha Dwi Khory; Bayu Budi Prakoso (Journal of Dedication in Community, 2026)
Addressing Indonesia's national target of 30% waste reduction by 2025, this study tackles the conventional "collect-transport-dispose" system in a suburban Sidoarjo village characterized by unsorted household waste. The objective was to enhance knowledge, attitudes, and skills in 3R (Reduce, Reuse, Recycle) principles to foster a zero-waste environment. Using a Participatory Action Research (PAR) methodology with 60 households, the program combined educational seminars with hands-on workshops on waste segregation and the construction of household-scale anaerobic composters. A comparative analysis of pre- and post-intervention surveys revealed significant improvements: community understanding of 3R concepts rose by 75%, routine waste segregation by 68%, and composting adoption reached 55%. This study concludes that the PAR approach is highly effective for initiating behavioral change in waste management. The program's success was driven by strengthening social capital and targeting perceived behavioral control, not just technical knowledge transfer. This initiative serves as a replicable micro-model for implementing a circular economy at the community level.